Produção e avaliação energética de briquetes a partir do resíduo da poda de espécies arbóreas de João Pessoa - Cavalcanti, Ingrid Lélis Ricarte (2020)
The resilience of natural resources and the quality of ecosystems have been compromised by population growth and economic demand. In addition, the rampant use of fossil fuels, added to their possible exhaustion, caused the openness to participation and studies in alternative energy sources and less impact on the environment. And, in the context of alternative sources, there is the reuse of organic solid waste as an energy raw material. In 2018, in the municipality of João Pessoa - Paraíba, 14,142.54 tons of pruning of urban afforestation were produced, which went to the landfill without any type of use or treatment. Configuring a waste of organic biomass load that can be applied in energy use. Thus, this work aimed to produce and evaluate the energy potential of briquettes made from the residues of arborea pruning in the municipality of João Pessoa - PB, using species of Ficus Bejamina, Castanhola, Algabora and the mixture of several others - the compound. For the results, the immediate composition of the biomasses, as well as the briquettes from them, were approached. Higher Calorific Value values of 18,589 MJ were found. Kg-1, 15,322 MJ. Kg-1, 15,798 MJ. Kg-1, 15,457 MJ. Kg-1, respectively, for the briquettes of algaroba, ficus, castanhola and compound, representing the amount of energy existing in them, conferring viability of use as solid fuel. The analytical results of the immediate composition of the residual biomass of pruning provide essential information to know if there is viability of its energy processing; And from the comparison between PCS values of the research with the literature, it was observed that the residues of afforestation pruning can be used as raw material for the production of briquettes, presenting possibilities of energy use. Therefore, it is concluded that understanding the potential of exotic species is of great value to realize the viability of their energy use. Furthermore, when such species are characterized as residues that, in the case of the municipality of João Pessoa, are inadequately disposed, because they are still passive for reuse. And according to the National Solid Waste Policy, all waste that is suitable for reuse should be destined for proper treatment, and energy treatment is a possibility.